Kinerja Breathing Wall sebagai Upaya Penurunan Suhu pada Bangunan (Studi Kasus: Masjid Al-Ikhlas dan Masjid Al-Fattah Sidoarjo) - Damayanti, Imanda Amalia; Wardoyo, Jono (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Humans spend 80–90% of their time indoors, and comfort and health are strongly influenced by building characteristics. In this case, comfort is related to air temperature and the factors that influence it, one of which is building wall design. Based on BMKG, Sidoarjo Regency is generally famous for its hot air conditions, with an average maximum air temperature in 2018–2023 reaching 33.8 °C. Al-Ikhlas and Al-Fattah mosques in Sidoarjo use breathing walls to reduce ambient temperature without the use of air conditioners. The difference in breathing wall characteristics between the two mosques can provide an overview of thermal performance. This study aims to determine the performance of comfortable temperature indicators on the on the breathing wall in reducing ambient temperature. The method used is a quantitative approach with air temperature measurements and visual observations in the form of breathing wall material type, breathing wall thickness, breathing wall color, and openings at Al-Ikhlas and Al-Fattah Mosques. The results showed that the Al-Ikhlas Mosque has a better comfortable temperature balance between the inside and outside spaces compared to the Al-Fattah Mosque. The highest temperature drop in the performance of the 2nd floor breathing wall occurred at the Al-Ikhlas Mosque (3.9 °C–4.3 °C) compared to Al-Fattah (3.5 °C). The high temperature drop in Al-Ikhlas is due to using a breathing wall with high thermal capacity, thick walls, bright breathing wall colors, and optimal openings. Keywords: breathing wall, mosque, temperature reduction